Turismo rural y desarrollo local en Cuba - Montiel Rodríguez, S.; Estévez Pazo, R.; Oliveros Blet, A. (Geographicalia, 2016)
Tourism in Cuba is a relatively recent phenomena. During the current decade, international tourism has increased more than a 17 percent. In the year 2.000, Cuba should receive more than 2 million tourists. In Cuba, rural tourism is practically not developed, the predominant models are the beach and the city tourism. In the world, rural tourism, and tourism in natural scenarios are conceived as development factors and as basic components for local development. In this article, an analysis of the possibilities of promote rural tourism in Cuba is done, related to the local development policies. A current study case is presented, on the municipality of Trinidad.